Impact of citizen participation in precarious housing resorption programs in Algeria (case of Sidi Slimane neighborhood, city of Boussaâda) - Yelles, Abdellatif; Khalfallah, Boudjemaa (Technium Social Sciences Journal, 2022)
Citizen and inhabitant participation in public interests has taken its importance over the last two centuries in Europe and the United States, and by the end of the 20th century, it had become central to debates around the issue of urban governance, social and urban development projects in particular. In recent decades, many countries have increasingly organizing collaborative governance, participatory budgeting and other models in which citizens can intervene more directly. It is emphasized that Algerian cities experienced a massive rural exodus during the 1990s for several reasons: insecurity, urban disparities and the attractiveness of services. This research studies the impact of citizen participation in programmers to reduce precarious habitat in the precarious neighborhood of Sidi Slimane in Boussaâda, a medium-sized city in the Algerian high plains. Since the end of the 1990s, this precarious neighborhood has undergone several operations aimed at improving its living environment, including the programme to reduce precarious habitat (PHR). The World Bank finances the latter in 2000, followed by a national programme of the same kind during the two decades that followed. Several modes, media and actors, essentially define citizen participation in these programmes: individuals, citizen entities, organizations and local authorities. In the field, it has been noted that each menu operation (rehousing, preservation, completion), is an experience conditioned by several dimensions (temporal, social, regulatory etc.). Therefore, the impact of citizen participation in these operations needs to be studied and arbitrated.